2023
DOI: 10.3389/froh.2023.1152601
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of oral microbiome acquisition in healthy infants: A pilot study

Abstract: ObjectivesThe human oral microbiota is one of the most complex bacterial communities in the human body. However, how newborns initially acquire these bacteria remains largely unknown. In this study, we examined the dynamics of oral microbial communities in healthy infants and investigated the influence of the maternal oral microbiota on the acquisition of the infant's oral microbiota. We hypothesized that the infant oral microbial diversity increases with age.MethodsOne hundred and sixteen whole-salivary sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…From another perspective on the oral microbiota and health, a recent report investigating the influence of the maternal oral microbiota on the formation of the oral microbiota in healthy infants suggested that infants may be colonized with an oral microbiota different from that of their mothers at birth. Further research is needed to determine how establishing an early oral microbiota influences health over time [ 51 ].…”
Section: Overview Of Factors Affecting the Oral Microbiotamentioning
confidence: 99%
“…From another perspective on the oral microbiota and health, a recent report investigating the influence of the maternal oral microbiota on the formation of the oral microbiota in healthy infants suggested that infants may be colonized with an oral microbiota different from that of their mothers at birth. Further research is needed to determine how establishing an early oral microbiota influences health over time [ 51 ].…”
Section: Overview Of Factors Affecting the Oral Microbiotamentioning
confidence: 99%
“…Genera such as Neisseria, Gemella, Granulicatella, Veillonella, Haemophilus, and Prevotella have been reported to increase at 3–6 months ( Cephas et al, 2011 ; Dzidic et al, 2018 ). With age, the infant oral microbiome increases in complexity and richness ( Sulyanto et al, 2019 ; Ramadugu et al, 2021 ; Li et al, 2023 ).…”
Section: Composition and Temporal Development Of The Infant Oral Micr...mentioning
confidence: 99%
“…The human microbiome is a complex ecosystem of microorganisms, undergoing substantial changes from birth to adulthood (1). Among the various microbiomes, the oral microbiome is one of the most intricate one, comprising over 700 identified species (2,3). The oral cavity is a primary entry point for the colonization of both oral and gastrointestinal tract (GIT), making it an accessible site for assessing microbial communities.…”
Section: Introductionmentioning
confidence: 99%